Strategi Koperasi Unit Desa “Tani Makmur” dalam Peningkatan Kesejahteraan Masyarakat di Kalurahan Tirtonirmolo Kecamatan Kasihan Kabupaten Bantul - Naufal Abdi Hanan; Oktarina Albizzia (SOSIO PROGRESIF | Media Pemikiran Studi Pembangunan Sosial, 2021)
The problem of poverty is a problem which until now has not been able to be overcome by the central government in general and regional governments in particular. Various ways to overcome this problem have been taken by the government but this problem has not been able to be resolved. This poverty arises because there is a lack of tools to fulfill basic needs or difficult access to education and employment. Therefore, researchers are interested in conducting research with the title Unit Strategy of the Village Cooperative "Tani Makmur" in Improving Community Welfare in Tirtonirmolo Village, Kasihan District, Bantul Regency, Yogyakarta. This study used descriptive qualitative method. The types of data used in conducting this research are primary data and secondary data. Data collection techniques used were observation, interviews, and documentation. The purpose of this research is to find out the Tani Makmur Village Unit Cooperative Strategy in Improving Community Welfare in Tirtonirmolo Village, Kasihan Subdistrict, Bantul Regency, Yogyakarta and to find out the constraints faced by the Tani Makmur Village Unit Cooperative in Improving Community Welfare in Tirtonirmolo Village, Kasihan District, Bantul Regency, Yogyakarta. Based on the research that has been done, the final results of the study stated that the Strategy of the Village Unit Cooperative "Tani Makmur" in improving welfare has been going well. Seen from the increasing number of people who joined the cooperative. With the quality of the management and good service from every business unit in KUD "Tani Makmur" KUD makes the community and members become more trusting. So that the goal of establishing the KUD to improve the welfare of the community and members is more or less achieved. There are several obstacles such as the lack of labor in the field, the lack of young people who are in KUD "Tani Makmur". The advice given is to increase the management's knowledge and skills, involve young people in management, and do more collaboration with other parties.